CLOSING THE LOOP ON CHRONIC PAIN WITH ECAP-CONTROLLED CLOSED-LOOP VS OPEN-LOOP SPINAL CORD STIMULATION: SYSTEMATIC AND LONGITUDINAL POOLED ANALYSIS OF THE EVOKE STUDY - Redyno, Muhammad Ananda Miftah; Cresma, Avisa Cetta; Putri, Ritma Ratri Ayunda (Journal of Pain, Headache and Vertigo, 2026)
Background: Chronic refractory back and leg pain is disabling and economically burdensome and, in Indonesia, disproportionately affects older adults who often face higher surgical risk due to multimorbidity, while long-term analgesic therapy is constrained by polypharmacy and adverse effects. Spinal cord stimulation (SCS) is a non-destructive alternative, yet adoption remains limited by affordability and reimbursement uncertainty within Indonesia’s national health insurance system where hospital payment is largely case-based (INA-CBG) and may not accommodate high upfront implant costs. Unlike open-loop SCS (OL-SCS), evoked compound action potential (ECAP)–controlled closed-loop SCS (CL-SCS) measures spinal cord responses to each pulse and automatically adjusts output to maintain targeted neural activation. We synthesized long-term head-to-head outcomes and appraised economic evidence to inform Indonesia-relevant decisions. Methods: Following PRISMA and PROSPERO registration (CRD420251126075), we targeted randomized, blinded, head-to-head trials of CL-SCS versus OL-SCS in adults with chronic intractable back and/or leg pain. EVOKE was the only eligible trial with a companion cost-utility analysis. Risk of bias was assessed with Cochrane RoB 2, and the economic model was appraised against CHEERS. Result: A total of 134 randomized participants were included. Overall risk of bias was low, with higher risk at 36 months due to missing data and selective reporting; the cost-utility model showed moderate-to-high quality yet was limited by reliance on a single trial. CL-SCS consistently outperformed OL-SCS with higher responder rates (≥50% pain relief RR 1.47 95% CI: 1.27–1.70; ≥80% pain relief RR 0.18, 95% CI 0.08–0.27) and lower overall pain scores (VAS mean difference −3.01, 95% CI −6.12–0.10). CL-SCS also produced greater improvements in disability, quality of life, stronger opioid reduction. The companion model projected higher QALYs at lower total costs for CL-SCS, with cost savings emerging around 5 years and a high probability of cost-effectiveness, although conclusions are limited by reliance on a single trial program and non-Indonesia cost inputs. Conclusion: ECAP-controlled CL-SCS provides superior, durable pain relief versus OL-SCS with supportive modeled value signals. For Indonesia—where older patients often face higher surgical risk and medication-related harms—these findings justify Indonesia-specific health technology assessment and INA-CBG–aligned budget impact analyses to evaluate affordability and define feasible coverage pathways. While these findings derive from a single randomized trial, confirmatory multicenter studies are warranted to validate and refine this approach for the management of chronic refractory back and leg pain.